CONTRIBUTION OF ISLAM IN THE WORLD (Case Study of Islamic Education Transmission) - Nurlathifah Thulfitrah B. (Pascasarjana UIN Alauddin Makassar, 2021)
Talking about the civilization of western, of course, it cannot be separated from the old history of Islam and the peak of its civilization. Before the power of science raised the spirits of western people who gave birth to the renaissance, Islam had experienced its golden age, while Europe was confined by the dark age. It reads a terrible condition, which Islam is busy with scientific studies so that it gives a civilization that has a very high value, unlike the western which closes rationality and relies on mystical. The spirit of moderation, liberation, and tolerance built by muslims, made westerners who chose to leave the old age free from pressure to make intellectual contact with muslim scholars. It is noted that they helped Islam a lot in translating Greek books into Arabic and translated by westerners into Latin. If you look closely, there is a common thread to connect these two different Qiblas. Muslims who reached the peak of glory in the Middle Ages, of course there was “interference” from other nations, such as the western. On the other hand, advanced western nations cannot be separated from the great contribution—consciously or unconsciously—by muslims in the past. Therefore, it is deemed necessary to recall Islam and its great contribution to the western world through Islamic education.